Utilizing Managed Pressure Drilling (MPD) technology to mitigate drilling problems in HPHT exploration wells - Md. Khalid, Mohd. Afiq (2015)
Managed Pressure Drilling (MPD) is a relatively new technology that has improved some old ideas of Underbalanced Drilling (UBD). The main aim of MPD discussed in this study is to avoid continuous influx of formation fluids to the surface by maintaining a state of effective overbalance. Nowadays, most of the remaining resources around the globe might only be located in harsh reservoir environment such as deepwater and high pressure high temperature (HPHT). This kind of situation also represents real threats to most drilling contractors, if conventional drilling methodology were applied. However, with MPD capability, it allows them to drill through the “un-drillable” formations, helps to reduce non-productive time (NPT) and overcome drilling problems such as narrow pressure window, kick-loss scenarios, low rate of penetration (ROP), loss of circulation, and failure to reach target depth (TD). These problems can be avoided if wellbore pressures are controlled, maintained and managed in more efficient way. However, in order to mitigate those challenges, implementing the right tools, techniques and necessary rig modification are crucial. In fact, during the MPD operation, controlling the wellbore breathing, and identifying the upper and lower limit of pore pressure were the main issues and concerned, which are also discussed. Lastly, conclusions are drawn and future recommendations are suggested in this study. In offshore Malaysia, MPD is proven to be a successful operation, while managed to drill through the HPHT condition, narrow pressure window, reach deeper target, control kick issues and minimize wellbore fatigue stress. Cross referencing with drilling contractors, and conducting verbal interview with drilling personnel are also recommended for furthering the study area.